2001
DOI: 10.1139/e01-031
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism of the Upper Cretaceous Nanaimo Group, southwestern Canadian Cordillera

Abstract: The Baja B.C. model has the Insular Superterrane and related entities of the Canadian Cordillera subject to >3000 km of northward displacement with respect to cratonic North America from ~90 to ~50 Ma. The Upper Cretaceous Nanaimo Group (on and about Vancouver Island, British Columbia) is a prime target to test the model paleomagnetically because of its locality and age. We have widely sampled the basin (67 sites from seven islands spread over 150 km, Santonian to Maastrichtian age). Most samples have low u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 25 publications
3
47
3
Order By: Relevance
“…Multiple lines of evidence point to between ~2,300 and 700 km of margin‐parallel translation during the Cretaceous for both arc‐related igneous and sedimentary rocks in northwestern Washington and southern British Columbia (i.e., Beck, ; Irving et al, ; Kim & Kodama, ; Miller et al, ; Wyld et al, ). Reconstructions based on known fault offsets place parts of the Coast Plutonic Complex‐North Cascades arc, WMB, Nanaimo Group, and components of the NWCS ~700 km to the south at the latitude of southern Oregon (Wyld et al, ), whereas models based on paleomagnetic data require ~2,000–1,700 km of translation from the latitude of the southern Sierra Nevada for the Nanaimo Group and the Methow terrane (Enkin et al, ; Kim & Kodama, ; Krijgsman & Tauxe, ; Rusmore et al, ). Rocks in southwestern Oregon have been correlated with parts of the NWCS based on lithologic and detrital zircon similarities (Brandon et al, ; Brown, ).…”
Section: Evolution Of the North Cascades Arc Systemmentioning
confidence: 99%
“…Multiple lines of evidence point to between ~2,300 and 700 km of margin‐parallel translation during the Cretaceous for both arc‐related igneous and sedimentary rocks in northwestern Washington and southern British Columbia (i.e., Beck, ; Irving et al, ; Kim & Kodama, ; Miller et al, ; Wyld et al, ). Reconstructions based on known fault offsets place parts of the Coast Plutonic Complex‐North Cascades arc, WMB, Nanaimo Group, and components of the NWCS ~700 km to the south at the latitude of southern Oregon (Wyld et al, ), whereas models based on paleomagnetic data require ~2,000–1,700 km of translation from the latitude of the southern Sierra Nevada for the Nanaimo Group and the Methow terrane (Enkin et al, ; Kim & Kodama, ; Krijgsman & Tauxe, ; Rusmore et al, ). Rocks in southwestern Oregon have been correlated with parts of the NWCS based on lithologic and detrital zircon similarities (Brandon et al, ; Brown, ).…”
Section: Evolution Of the North Cascades Arc Systemmentioning
confidence: 99%
“…Apart a few exceptions [ Kodama and Davi , ; Dickinson and Butler , ; Tan and Kodama , ; Enkin et al ., ; Kim and Kodama , ; Piguet et al , ], turbidites have been ruled out from paleomagnetic records, as they represent geologically instantaneous deposits. In a recent investigation of upper Eocene‐lower Oligocene weakly deformed turbidites exposed in Haute‐Savoie (France), the authors [ Piguet et al ., ] mentioned that a suitable characteristic remanence was preserved and likely acquired early after deposition in levels that contain magnetite.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of data from known offsets on identified faults, lithologies, and reconstructions based on paleomagnetic data has been used to argue that the rocks of the North Cascades were translated from more southerly latitudes to their present position. However, the various models suggest a wide range of points of origin and thus amounts of translation: (1) ~700 km from the latitude of the Klamath Mountains and northern Sierra Nevada (Brandon et al, 1988;Garver, 1988;Wyld et al, 2006); (2) ~1600 km from the latitude of the southern end of the Sierra Nevada batholith (Umhoefer, 2003;Kim and Kodama, 2004;Umhoefer and Blakey, 2006); or (3) ~2300-2500 km at the latitude of northern Mexico during the mid-Cretaceous ("Model B" of Cowan et al, 1997; "Baja-BC" hypothesis; Beck and Noson, 1972;Enkin et al, 2001).…”
Section: Paleogeographic Implicationsmentioning
confidence: 99%
“…Early paleomagnetic studies of the Cretaceous plutonic and sedimentary rocks suggested that the Insular superterrane and Coast Plutonic Complex-North Cascades formed ~2500-3000 km to the south relative to the North American craton and were translated to the north between ca. 90-55 Ma (the "Baja-BC" hypothesis; Beck et al, 1981;Umhoefer, 1987;Ague and Brandon, 1996;Enkin et al, 2001). More recent paleomagnetic studies interpret moderate (~1600-2000 km) translation of these same rocks from reconstructions based on a combination of corrections to the paleomagnetic data and known fault offsets (Kim and Kodama, 2004;Krijgsman and Tauxe, 2006;Umhoefer and Blakey, 2006;Rusmore et al, 2013).…”
Section: Introductionmentioning
confidence: 96%